2008
DOI: 10.1115/1.2900726
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Kinematics, Kinetics, and EMG Throughout Wheelchair Propulsion in Able-Bodied and Persons With Paraplegia: An Integrative Approach

Abstract: A systematic integrated data collection and analysis of kinematic, kinetic, and electromyography (EMG) data allow for the comparison of differences in wheelchair propulsion between able-bodied individuals and persons with paraplegia. Kinematic data from a motion analysis system, kinetic data from force-sensing push rims, and electromyography data from four upper-limb muscles were collected for ten push strokes. Results are as follows: Individuals with paraplegia use a greater percentage of their posterior delt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…The semicircular technique is used widely in experienced wheelchair users, while nonusers implemented the arcing technique [38]. Results gained from studies with nondisabled subjects demonstrated the validity and reliability of EMG data in the measurement of muscle activity; the findings of the present study are certainly in-line with earlier research [39][40]. The level and timing of muscle recruitment in people who actually need to use a wheelchair are bound to show considerable variations depending on the type and level of each individual's injury [34].…”
Section: Discussionsupporting
confidence: 82%
“…The semicircular technique is used widely in experienced wheelchair users, while nonusers implemented the arcing technique [38]. Results gained from studies with nondisabled subjects demonstrated the validity and reliability of EMG data in the measurement of muscle activity; the findings of the present study are certainly in-line with earlier research [39][40]. The level and timing of muscle recruitment in people who actually need to use a wheelchair are bound to show considerable variations depending on the type and level of each individual's injury [34].…”
Section: Discussionsupporting
confidence: 82%
“…The high incidence of shoulder pain in MWUs as compared to the general population may be the result of muscle activity differences as evidenced in our prior study (Dubowsky et al, 2008); however, further investigation into the connection between this link cannot be achieved without the aid of a computational model. The use of a fully validated patient-specific upper limb model will allow for the quantification of the magnitude of shoulder joint forces.…”
Section: Introductionmentioning
confidence: 86%
“…Investigating the magnitude of shoulder joint forces throughout propulsion may provide insight into the potential cyclic-propulsion and cumulative-trauma link. We have taken a two-pronged approach to investigate this possible connection, the first, looking at differences in experimentally collected data between able-bodied individuals and individuals with paraplegia (Dubowsky et al, 2008), and the second-the focus of the current study-creating and validating a computational upper-body model of WC propulsion for use in investigating the magnitude of shoulder joint forces.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, unnatural joint motion and stresses occur at the shoulder joint, increasing risk of pain and injury. 3,4 It is clear that continuous pushing, a common rehabilitation and post-rehabilitation therapeutic exercise, leads to agonistantagonist fatigue imbalance both acutely and chronically; however, the effects of alternative therapeutic exercises on fatigue imbalance, such as wheelchair sport, are just starting to be explored. It is unknown if wheelchair sport activity leads to greater, similar or lesser imbalance than typical therapeutic exercise (that is, continuous pushing).…”
Section: Introductionmentioning
confidence: 99%